Modernity, Islam, and secularism in Turkey: bodies, places, and time - Çınar, Alev (Public worlds, 2005)
Introduction -- Performative politics and the public gaze -- Clothing the national body: Islamic veiling and secular unveiling -- Cities, squares and statues: the use of public space in the making of the nation -- Performing the nation: public contestations of national history -- Conclusion -- Notes -- Bibliography -- Index